CARBON EMISSION DISCLOSURE IN ENVIRONMENTAL MANAGEMENT ACCOUNTING PRACTICES (Indo Tambangraya Megah Tbk Study) - Puspita, Dyah Aruning; Habibi Amarullah; Djoko Sugiono (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
This research aims to determine and analyze carbon emissions in the sustainability report for the 2020-2022 period of Indo Tambangraya Megah Tbk. (ITMG). The variable in this research is the reporting of Carbon Emissions in sustainability reports. The population in this study was Indo Tambangraya Megah Tbk. (ITMG) for the 2020-2022 period, which was selected based on certain criteria. The analysis carried out is to identify how well the Carbon Emission Disclosure Checklist is implemented in the sustainability report of the object under study. Results of analysis of Indo Tambangraya Megah Tbk. (ITMG) shows that every year carbon emissions reporting is always carried out and there are improvements in several aspects by the company Indo Tambangraya Megah Tbk. (ITMG) which indicates that from year to year the company's concern for the environment or the sustainability performance of the company Indo Tambangraya Megah Tbk. (ITMG) experienced an increase. It is hoped that the results of this research can become knowledge and consideration for investors in investing.